Change in ecological stoichiometry of Carex brevicuspis in response to seasonal dynamics and elevation in Dongting Lake, China. (26th July 2018) - Fu, Xiaohua; Li, Feng; Zhu, Lianlian; Xie, Yonghong; Hu, Cong; Chen, Xinsheng; Deng, Zhengmiao
Abstract : Plant nutrient stoichiometry is affected by both environmental factors and plant physiological processes. However, we know little about how small elevation gradients (influencing e.g. flooding regimes) and seasonality combine with soil physicochemical properties to influence nutrient stoichiometry in wetland plants. In this study, we examined these factors in Carex brevicuspis at Dongting Lake, China, during the non‐flooding periods in March, May and December of 2015 and February of 2016. We found that total foliar C concentration increased as elevation increased, especially during December 2015 and February 2016. At the low‐elevation site, total foliar C concentration decreased over the season, whereas it first increased and then decreased over time at higher elevations. Foliar total N and P concentrations decreased from March to May and subsequently increased throughout the season, and these concentrations were always much higher at the low‐elevation site. The C:N and C:P ratios first increased and then decreased over the season, while increasing with rising elevation. The N:P ratio was lower at the low‐elevation site, especially during May 2015 and February 2016; its variation over time differed across the elevations. A canonical correspondence analysis revealed that soil organic C, total N and soil nitrate N are important for determining C. brevicuspis stoichiometry. Our results suggest that both elevation and plant life stage have a significant influence on plant stoichiometry. This study improves our understanding of the seasonal dynamics of plant nutrients under different geographical conditions.